2006
DOI: 10.2135/cropsci2006.02.0092
|View full text |Cite
|
Sign up to set email alerts
|

Response of Chickpea Yield to High Temperature Stress during Reproductive Development

Abstract: Minimizing the exposure of an annual crop to abiotic stresses may increase seed yield. A study was conducted to determine the effect of high temperature stress during reproductive development on pod fertility, seed set, and seed yield of chickpea (Cicer arietinum L). 'Myles' desi and 'Xena' kabuli chickpea were grown in a controlled environment under 20/16°C day/night air temperatures (control). High (35/16°C) and moderate (28/16°C) temperature stresses were imposed for 10 d during early flowering and pod deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 39 publications
3
112
0
4
Order By: Relevance
“…Kabuli types have greater pod abortion than desi type (Leport et al, 2005). Wang et al (2006) also reported that moisture stress was more damaging to kabuli type as compared to desi chickpea.…”
Section: Plant Wilting-iimentioning
confidence: 92%
See 1 more Smart Citation
“…Kabuli types have greater pod abortion than desi type (Leport et al, 2005). Wang et al (2006) also reported that moisture stress was more damaging to kabuli type as compared to desi chickpea.…”
Section: Plant Wilting-iimentioning
confidence: 92%
“…The kabuli type chickpea were found more sensitive to high temperature and moisture stress than desi chickpea. Wang et al (2006) had also found significant variation in desi and kabuli type chickpea in response to moisture and high temperature stress. This was due to the reason that kabuli types are adapted to Mediterranean region and therefore is more sensitive to high temperature and drought as compared to desi type (Leport et al, 2006).…”
Section: Plant Wilting-imentioning
confidence: 99%
“…Chickpea is sensitive to high temperature stress (Wang et al 2006), hence the present studies were undertaken to find out the extent of damage caused by heat stress to chickpea plants at early vegetative growth and to probe the involvement of proline in mediating its heat sensitivity. Our observations indicated that the germination and growth of the chickpea seedlings were significantly inhibited with increase in temperature to 40/35°C and 45/ 40°C.…”
Section: Effects Of Heat Stressmentioning
confidence: 99%
“…Due to changing climate, the exposure of chickpea to high temperature in terms of intensity and duration is expected to increase leading to reduction in its potential yield. Previous reports have indicated adverse effects of high temperature on chickpea (Summerfield et al 1984;Wang et al 2006). Thus, effective measures are needed to counter the negative effects of high temperature on this crop.…”
Section: Introductionmentioning
confidence: 99%
“…Drastic reductions in chickpea seed yields were observed when plants at flowering and pod development stages were exposed to high (35°C) temperatures (Summerfield et al, 1984). Wang et al (2006) exposed various chickpea lines at pre-flowering and pod formation stage under higher temperature and observed maximum yield damage by 59% due to higher temperature at pod formation stage as compared to 34% yield reduction at pre-flowering stage. The negative effect of high temperature on grain yield is expected to increase due to global warming.…”
Section: Introductionmentioning
confidence: 99%